2012
DOI: 10.5402/2012/596029
|View full text |Cite
|
Sign up to set email alerts
|

High-Grade Prostate Cancer: Favorable Results in the Modern Era Regardless of Initial Treatment

Abstract: Purpose. We performed a retrospective study to determine the outcome of a modern cohort of patients with high-grade (Gleason score ≥ 8) prostate cancer treated with radical prostatectomy, radiation therapy, or hormone therapy. Methods. We identified 404 patients in the South Texas Veteran's Healthcare System Tumor Registry diagnosed with high grade prostate cancer between 1998 and 2008. Mean follow-up was 4.62 ± 2.61 years. End points were biochemical failure-free survival, overall survival, metastasis-free su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…However, the 5-year BF rate for the RT group is more than twice our calculated rate of 7.2%. This discrepancy is most likely due to 95.8% of RT patients in our study receiving ADT, compared to 50.8% in the referenced study [ 15 ]. RT with 2-3 years of ADT is now a NCCN category 1 recommendation for patients with a high-risk of recurrence [ 1 ] based on randomized trial data showing decreased rates of clinical progression and increased overall survival compared to patients not receiving ADT [ 17 ].…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…However, the 5-year BF rate for the RT group is more than twice our calculated rate of 7.2%. This discrepancy is most likely due to 95.8% of RT patients in our study receiving ADT, compared to 50.8% in the referenced study [ 15 ]. RT with 2-3 years of ADT is now a NCCN category 1 recommendation for patients with a high-risk of recurrence [ 1 ] based on randomized trial data showing decreased rates of clinical progression and increased overall survival compared to patients not receiving ADT [ 17 ].…”
Section: Discussioncontrasting
confidence: 67%
“…Even fewer studies have compared the biochemical and metastatic outcomes of patients with GS ≥ 8 disease treated with RP versus RT + ADT. Two retrospective studies have investigated outcomes of patients with GS ≥ 8 [ 15 , 16 ]. Ramahi et al reported 5-year distant metastasis and 5-year RP BF rates similar to our current study [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation